Examination of pre-service physics teachers' epistemologies of scientific models and their model formation during model-based inquiry process - (:unkn) unknown (The Education University of Hong Kong, 2018)
The purpose of this study was to evaluate pre-service teachers' epistemologies of scientific models and their model formation in a model-based inquiry environment. Theoretical underpinnings of this paper are the following: Pre-service teachers' epistemologies of models are structured as their beliefs, can be reshaped by instructional experiences, and may have relationship with their practice i.e. model building. One group pre-test post-test experimental design using quantitative and qualitative research methods was carried out for the study. Correlational research design was also used. The conclusions drawn from the study are as follows: First, model building and formation in inquiry facilitate changes in students' epistemic reasoning around models and enrich their understanding of what a model is, what it may be used for, and how models are built and changed. Second, instructional focus on scientific models and model based investigations influences students' reconceptualization about models and supports a shift in nature, function and inquiry role of their models. As a result, students can develop models of natural phenomena, test and revise their models and gather evidence for explanations. Finally, modelbased inquiry provides bridging the gap between belief and practice so that students can reflect their epistemologies into their models. © 2018 EdUHK APFSLT.
Keywords: Epistemology; Model formation; Model-based inquiry; Pre-service teachers